Political Conflict and Violence in Nigeria 1960-2010: A SYNOPSIS - Okoro, S. I.; Omeje, P.U (EBSU Journal of Social Sciences and Humanities, 2021)
By its very nature, politics is conflictual. This is because the essential ingredient of politics is struggle and pursuit of interest. Hence a commentator defined politics as the struggle for the acquisition of state power, the consolidation of state power and the use of state for the advancement of group interest. Though the above commentator failed to realize that politics transcends the state to include all oth er arenas of group interaction over commonly held resources-the church, family, social/communal groups, even ethnicities; that the central issue of struggle and pursuit of interest is highlighted makes it acceptable nonetheless. In Nigeria, as elsewhere, political interactions between and among the various groups and interest have always tended to conflicts, even violence. Need this be so? While we acknowledge the centrality, even inevitability of conflicts in Politics we are persuaded that poli tical conflicts can, and should be resolved without resources to violence. In this synopsis, attempt is made to highlight some of the major political conflicts that have attended independent Nigeria-1965 Western Regional Elections, coup and counter coup of 1966, the civil war, the annulment of 1992 presidential elections, the ill-health of president Umaru Musa Yar’adua etc with a view to determining alternative approaches to their resolution, short of violence. A panoramic presentation, this pap er hopes to proffer workable solution to the recurrent Political conflicts and violence in Nigeria since independence.